2017
DOI: 10.1161/strokeaha.116.014561
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Positive Troponin and Echocardiogram Findings and Association With Mortality in Acute Ischemic Stroke

Abstract: Background and Purpose Acute ischemic stroke (AIS) patients may have raised serum troponin (cTn) levels on admission, although it is unclear what prognostic implications this has, and whether elevated levels are associated with cardiac causes of stroke or structural cardiac disease as seen on echocardiogram. We investigated the positivity of cTn and echocardiogram testing within a large biracial AIS population, and any association with post stroke mortality. Methods Within a catchment area of 1.3 million we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 34 publications
(49 reference statements)
4
52
0
Order By: Relevance
“…Dynamic changes of hs‐cTn levels in AIS patients are associated with unfavorable outcomes, including death . In line with previous studies of circulating cTnT, assessed with conventional or high‐sensitivity assay, we confirmed the elevation of serum hs‐cTnT is predictive of mortality in AIS patients. Unfortunately, patient information regarding the serial measurement of hs‐cTnT in this study was incomplete for statistical analysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dynamic changes of hs‐cTn levels in AIS patients are associated with unfavorable outcomes, including death . In line with previous studies of circulating cTnT, assessed with conventional or high‐sensitivity assay, we confirmed the elevation of serum hs‐cTnT is predictive of mortality in AIS patients. Unfortunately, patient information regarding the serial measurement of hs‐cTnT in this study was incomplete for statistical analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, clear evidence indicates that cardiac lesions can be observed following nervous system insults . Increased levels of cardiac troponin (cTn), as a strong indicator of cardiac injury, have been repeatedly reported to be associated with adverse outcomes in AIS patients . Cardiac troponins exist as structural proteins in a small free pool in cardiomyocytes, and will be released in a complex form of subunits after disease conditions .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic yield of FOCUS in the ED in our study was similar to that of several previous studies of TTE in other populations. In a recent study of more than 1000 patients with acute ischemic stroke, Wrigley et al found the prevalence of positive findings on echocardiography that “could possibly impact future management decisions,” including an EF of 35% or lower and an intracardiac thrombus, among others, was 10.7%. The yield of routine screening for first‐degree family members of patients with bicuspid aortic valves was 10.1% .…”
Section: Discussionmentioning
confidence: 99%
“…When the concomitant myocardial infarction (3,5%) was excluded from hypertroponinemia was also associated with increased mortality at 1 (35%) and 3 years (60%). 6 The results from this elegant and sophisticated statistical model evidence that the increase of cTn in patients with structural heart disease and who suffered a stroke has the highest risk of mortality. However, the results cannot be interpreted as if they reflected the real picture throughout the world.…”
mentioning
confidence: 93%
“…To this regard, Wrigley et al 6 analyzed data of biracial population of 1.3 million is largely representative of the United States in terms of median age, proportion of black subjects, and economic status. The analysis was done in adult patients (aged 20 years and older) with AIS who presented to an emergency department.…”
mentioning
confidence: 99%